Capacity of apatite formation of thin films of hydroxyapatite modified by laser ablation - Mizuno, Andrea Muñoz; Daza-Cuadros, Jenny Paola; Quintero-Quiroz, Carlos Eduardo; Peña-Ballesteros, Darío Yesid; Sandoval-Amador, Anderson Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In this work, the effect of the modification by laser ablation of hydroxyapatite surfaces synthesized by sol-gel on the capacity of apatite formation by in vitro tests was analyzed. For this, layers of sodium titanate were grown on disks of the Ti6Al4V alloy by immersion in 10 M NaOH at 60 ° C for 24 hours. The hydroxyapatite coatings were then prepared using calcium nitrate tetrahydrate and triethyl phosphite as precursors by the sol-gel method and the dip-coating technique. Finally, patterning was performed by means of an Nd: YAG laser, with working energy of 1.3 mJ. Hydroxyapatite was evaluated and characterized using X-Ray Diffraction, Scanning Electron Microscopy and Dispersive X-ray Energy Spectroscopy techniques. In order to evaluate the reactivity, immersion in simulated body fluid was carried out and calcium atomic absorption analysis was carried out to observe the dissolution and precipitation phenomena of this ion, and it was determined that the samples treated at 600 ° C They induced a better response to the growth of apatites, however, all the coatings have characteristics that would allow these coatings to be used as implants in bone substitutes.